2021
DOI: 10.1002/chem.202004865
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ex and In Situ Measurements Elucidate the Dynamics of Retained Species in ZSM‐5 and SAPO‐18 Catalysts Used in the Methanol‐to‐Olefins Reaction

Abstract: The dynamics of the retained species on ZSM‐5 and SAPO‐18 catalysts are studied by using a combination of temperature‐programmed desorption/oxidation, ex situ analysis, and in situ FTIR spectroscopic measurements over the entire conversion range, using fixed‐bed and spectroscopic cell reactors, in continuous and discontinuous mode. The results point to the appropriateness of the combined methodologies to track the interconversion of active into deactivating species. A statistically relevant (supported by linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…In general, the bands in the υ C‐H and υ C=C bond regions present less absorbance intensities for the feed of methanol‐water, whereas the bands in the υ O‐H and δ O‐H regions are more intense due to the high water concentration in the reaction medium. In a previous works, [40,59] we observed that the bands in the υ C=C and δ C‐H regions are more reliable to study the retained species as they are less affected by gaseous phase or physisorbed species. The results clearly show that these bands (representative of retained species) are less intense for the feed of methanol‐water, indicating that co‐feeding water disfavors the formation of retained species as also observed in the experiments carried out using UV‐vis spectroscopy.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In general, the bands in the υ C‐H and υ C=C bond regions present less absorbance intensities for the feed of methanol‐water, whereas the bands in the υ O‐H and δ O‐H regions are more intense due to the high water concentration in the reaction medium. In a previous works, [40,59] we observed that the bands in the υ C=C and δ C‐H regions are more reliable to study the retained species as they are less affected by gaseous phase or physisorbed species. The results clearly show that these bands (representative of retained species) are less intense for the feed of methanol‐water, indicating that co‐feeding water disfavors the formation of retained species as also observed in the experiments carried out using UV‐vis spectroscopy.…”
Section: Resultsmentioning
confidence: 68%
“…Interestingly, the intensity of the 1390 (δ C-H ) and 1591 (υ C = C ) cm À 1 bands decreases so much for the methanol-water feed that it seems to be practically absent, whereas the 1570 cm À 1 band becomes more dominant in the region of retained species. According to the literature, [59,60] the simultaneous rise of the 1390 and 1591 cm À 1 bands can be related to absorbed olefins. The presence of olefins within the retained species in SAPO-34 catalysts was demonstrated using Raman spectroscopy by Rojo-Gama et al, [61] being a finding applicable to our results since the SAPO-18 structure is relatively similar to that of SAPO-34.…”
Section: In-situ Analysis By Ftir Spectroscopymentioning
confidence: 98%
“…In the case of HT-SC coke species released at higher temperature (maximum rate at 500 ºC) greater amount was observed for Cat− Z30 in comparison with Zeo− Z30 catalyst. The species removed during the TPD of zeolite catalysts deactivated in the cracking of hydrocarbons [56] and methanol-to-olefins (MTO) reactions [57] have been previously ascribed to coke precursors. However, these species could be also the consequence of the aging (dehydrogenation and decomposition reactions) that hard coke may undergo under N 2 atmosphere at high temperature [58].…”
Section: Content and Nature Of Cokementioning
confidence: 99%
“…The use of operando spectroscopy partnering with ab initio calculations has revealed steps of initiation, autocatalysis, and deactivation [12][13][14][15][16][17][18][19] during MTH/MTO reactions. In brief, acid sites are prone to form methoxy and carbocation species that dehydrate, oligomerize or alkylate/dealkylate (methylate), cyclize, and aromatize to form a whole range of products, including deactivating species [20][21][22][23][24][25][26][27][28][29]. Thus, the active site is the combination of the acid site and the adsorbed carbocation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous experience has demonstrated that two commercial gas-solid spectroscopic cells are suitable to study the formation kinetics of species on the catalyst surface during the MTH reaction with different catalysts [22,24,50] or cofeeding water [23,51] using FTIR or UV-vis spectroscopies. Accordingly, we verified that the formation rates of species decrease with a decreasing acid concentration in the catalyst and an increasing water concentration in the feed, which are the expected kinetic observations.…”
Section: Introductionmentioning
confidence: 99%